آليات التدريب على مهارة التحدث في رياض الأطفال دراسة ميدانية في بعض رياض الأطفال لولاية الوادي - بوضبية, مصباحي, زينب بشيرة; زاوش, شويخة (Univercty of Eloued, 2020)
يسعىبحثناهذالدراسةآلياتالتدريبعلىمهارةالتحدثفيرياضالأطفال،وتعدمهارةالتحدثأهمالمهاراتالتيتساهمفيإكتساباللغة . وقدإتبعناالمنهجالوصفيمتخذينمنالتحليلوالإحصاءأداةإجرائية،حيثتمالإستفادةمنخبراتمجموعةمنمربيات. وقدتمتوزيعالإستبياناتالخاصةبالأبوين،والمربياتفيعدةبلدياتتابعةلولايةالوادي Our research seeks to study the mechanisms of speaking skill training in kindergarten, and speaking skill is the most important skill that contributes to language acquisition. We followed the descriptive approach, using analysis and statistics as a procedural tool. The experiences of a group of educators were used. The questionnaires for parents and nannies were distributed in several municipalities in the state of the Valley
Keywords: آليات التدريب – مهارة التحدث – رياض الأطفال; Training Mechanisms - Speaking Skill - Kindergarten